EFL Teachers Perception on Postmehod Pedagogy in Higher Education Context in Indonesia - Ani Fiani; Syaprizal Syaprizal (Linguistic, English Education and Art (LEEA) Journal, 2018)
This current study is aimed to investigate EFL teachers perception on postmethod pedagogy proposed by Kumaravadivelu. To achieve the aim, the research method used here is a qualitative case study with nine doctoral students from various universities in Indonesia. The data collection tools are a questionnaire and structured interview. The result revealed that most of the EFL lecturers have already implemented postmethod pedagogy perspective divided into four parts: teaching interaction, teaching strategy, teaching objective, and teaching content although they were not aware yet about the concept. It was indicated that they theorized what they do and did what they theorize. For further researchers, postmethod pedagogy should be investigated in real condition of teaching and learning process and the effect of this pedagogy on students learning achievement so that it will be clearly found whether or not this pedagogy perspective is appropriate to be implemented in higher education in Indonesian context. Keywords: postmethod pedagogy, postmethod pedagogy framework, EFL teachers